Perancangan Interior Kantor PT PLN (Persero) Pembangkitan Sumbangsel Sektor Bengkulu - ANGGRAENI, Irma Putri (Jur DI FSR ISI Yogyakarta, 2016)
Office of PT PLN (persero) Southern Sumatera generator sector of Bengkulu is an office which operates power electricty with generator units in the Bengkulu. Motivated by the need of electricity for extracting gold in the Lebong Tandai and Muara Aman area. Then in 1912-1923 of the Dutch East Indies Kolonial Goverment was building two units of PLTA in the village of Turan Tiging, Tes and begin operating in 1923. Hydroelectric (PLTA) is one of the oldest hydropower plant in the Indonesia.Main purpose redesign the office of PT PLN (persero) Southern Sumatera generator sector of Bengkulu is the one of want to show the character and identity of the PT PLN company as power electricty service in Indonesia with take designing from the Company’s logo then is tranformed. The design method which is used to get the proper concept is “Mapping Concept Design” by analyzing the problem and then solved. The problem that arises is how to create the atmosphere of the office of PT PLN (Persero) generation Southern Sumatera of sector Bengkulu is expected making the servants be interested from the character, profile and criteria of the Company by providing the impression of a comfortable and natural.To achieve the concept which is expected then redesign the office of PT PLN (persero) Southern Sumatera generator sector of Bengkulu transform the PLN’s logo as well as the idea and style use Modern Industrial design with the theme is “Ligthing as identity”.Key word : PT PLN (persero) Southern Sumatera generator sector of Bengkulu, logo of PT PLN (persero), Modern Industrial.